A fatal case of Exophiala dermatitidis disseminated infection in an allogenic hematopoietic stem cell transplant recipient during micafungin therapy. Issue 6 (June 2019) - Hagiya, Hideharu; Maeda, Tetsuo; Kusakabe, Shinsuke; Kawasaki, Keisuke; Hori, Yumiko; Kimura, Keigo; Ueda, Akiko; Yoshioka, Nori; Sunada, Atsuko; Nishi, Isao; Morii, Eiichi; Kanakura, Yuzuru; et al.
Abstract: Exophiala dermatitidis is a dematiaceous fungus that is increasingly becoming the cause of fungal infection in immunocompromised patients. However, the risk factors and optimal treatment modality for E. dermatitidis infection are unknown to date. Herein, we present a fatal case of E. dermatitidis infection in an adult patient that developed after allogeneic hematopoietic stem cell transplantation for chronic active Epstein-Barr virus infection. The dematiaceous fungus caused a breakthrough fungemia despite prophylactic administration of micafungin. Although the patient was intensively treated with liposomal-amphotericin B and voriconazole, serum level of beta-D-glucan continuously increased, and the patient eventually died because of cerebral hemorrhage. An autopsy found multiple involvements of the fungal infection at the bilateral lungs, thoracic cavities, diaphragm, and thyroid. To the best of our knowledge, this is the first reported case of E. dermatitidis infection involving these tissues as determined via autopsy. This case highlights the importance of attention for Exophiala infection in immunocompromised individuals in those given antifungal therapy with echinocandins.